Targeted clearance of p21‐ but not p16‐positive senescent cells prevents radiation‐induced osteoporosis and increased marrow adiposity. Issue 5 (1st April 2022) - Chandra, Abhishek; Lagnado, Anthony B.; Farr, Joshua N.; Doolittle, Madison; Tchkonia, Tamara; Kirkland, James L.; LeBrasseur, Nathan K.; Robbins, Paul D.; Niedernhofer, Laura J.; Ikeno, Yuji; Passos, João F.; Monroe, David G.; et al.
Abstract: Cellular senescence, which is a major cause of tissue dysfunction with aging and multiple other conditions, is known to be triggered by p16 Ink4a or p21 Cip1, but the relative contributions of each pathway toward inducing senescence are unclear. Here, we directly addressed this issue by first developing and validating a p21 ‐ ATTAC mouse with the p21 Cip1 promoter driving a "suicide" transgene encoding an inducible caspase‐8 which, upon induction, selectively kills p21 Cip1 ‐expressing senescent cells. Next, we used the p21 ‐ ATTAC mouse and the established p16 ‐ INK ‐ ATTAC mouse to directly compare the contributions of p21 Cip1 versus p16 Ink4a in driving cellular senescence in a condition where a tissue phenotype (bone loss and increased marrow adiposity) is clearly driven by cellular senescence—specifically, radiation‐induced osteoporosis. Using RNA in situ hybridization, we confirmed the reduction in radiation‐induced p21 Cip1 ‐ or p16 Ink4a ‐driven transcripts following senescent cell clearance in both models. However, only clearance of p21 Cip1 +, but not p16 Ink4a +, senescent cells prevented both radiation‐induced osteoporosis and increased marrow adiposity. Reduction in senescent cells with dysfunctional telomeres following clearance of p21 Cip1 +, but not p16 Ink4a +, senescent cells also reduced several of the radiation‐induced pro‐inflammatory senescence‐associated secretory phenotype factors. Thus, by directly comparing senescent cell clearance using two parallel genetic models, we demonstrate that radiation‐induced osteoporosis is driven predominantly by p21 Cip1 ‐ rather than p16 Ink4a ‐mediated cellular senescence. Further, this approach can be used to dissect the contributions of these pathways in other senescence‐associated conditions, including aging across tissues. Abstract : We generated a new mouse model ( p21‐ATTAC ) for clearance of senescent cells expressing p21 Cip1 . Clearance of p21 Cip1 ‐expressing senescent cells, but not of p16 Ink4a ‐expressing cells, prevented bone loss following focal radiation. The genetic approach described here can be used to dissect the contributions of p21 Cip ‐ versus p16 Ink4a ‐driven cellular senescence in other senescence‐associated conditions, including aging across tissues.